Pengaruh Integritas, Efisiensi Kerja, dan Karakteristik Pekerjaan terhadap Kinerja Aparatur Desa dengan Komitmen Organisasi sebagai Variabel Intervening (Studi Kasus Se-Kecamatan Wanasari) - Faninda Ayu Khumaeroh; Ari Kristiana; Slamet Bambang Riono; Hendri Sucipto; Muhammad Syaifulloh (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to examine the influence of integrity, work efficiency, and job characteristics on the performance of village apparatus, with organizational commitment serving as a mediating variable. The research was conducted among village officials in Wanasari District, Brebes Regency, involving 109 respondents selected using a quantitative approach through questionnaire-based data collection. The data were analyzed using SmartPLS. The results of the path coefficient analysis indicate that integrity has a positive effect on organizational commitment, with a coefficient value of 0.286. Work efficiency also exerts a positive influence on organizational commitment, with a coefficient of 0.215, suggesting that officials who complete tasks efficiently and accurately tend to demonstrate higher levels of commitment. Job characteristics, such as role clarity and task challenge, also contribute positively to organizational commitment, with a coefficient of 0.138. Furthermore, integrity, work efficiency, and job characteristics each have a direct impact on the performance of village officials, with coefficient values of 0.086, 0.167, and 0.088, respectively. Notably, organizational commitment plays a significant mediating role, with a direct effect on performance amounting to 0.206. These findings underscore the importance of organizational loyalty and a strong sense of institutional belonging in enhancing the effectiveness of village apparatus. Strengthening organizational commitment emerges as a critical factor in maximizing the impact of integrity, work efficiency, and job characteristics on performance outcomes.